Massive ossifying pleomorphic adenoma of the maxillary antrum: A rare presentation - Debarati Ray; Dibyendu Mazumder; Jaygopal Ray; Sourav Bhattacharya (Wolters Kluwer Medknow Publications, 2015)
Pleomorphic adenoma is the most common benign neoplasm of salivary gland origin involving both major and minor glands. Though parotid is the most common site of origin, it has been reported to arise from various unusual locations. Incidence of its origin in the respiratory tract is extremely rare, and the occurrence is even lower in the maxillary sinus. We report a case of a huge antral pleomorphic adenoma in a 33-year-old male patient presented as a swelling in the maxilla which was mistaken of odontogenic origin. Histological findings showed extensive ossification and hyalinization of the stroma as a striking feature. The patient has undergone hemimaxillectomy and is in 8 months follow-up without any sign and symptom of recurrence.